MODEL LITERASI INFORMASI BAGI MAHASISWA BARU DI PERPUSTAKAAN UNIVERSITAS KRISTEN SATYA WACANA SALATIGA JAWA TENGAH - NARENDRA, ALBERTOES PRAMOEKTI (Jurnal Ilmiah Widya Sosiopolitika; Vol 2 No 1 (2020): ISU PARIWISATA DAN KESEHATAN DALAM PERSPEKTIF SOSIAL DAN POLITIKDO - 10.24843/JIWSP.2020.v02.i01.p06, 2020)
ABSTRACT This research was conducted to determine the ability of new students to recognize information sources and use information, especially at Satya Wacana Christian University through an information literacy program implemented by the Library. The method used in this research is descriptive qualitative study of existing literature and documents. Information literacy program for new students is carried out in order to provide knowledge and experience in the way of learning in universities that are different from those at the high school level. The results of this research include the application of information literacy models whose elements are contained in information literacy models that are currently known globally. Keywords : information literacy, students, SWCU Library, learnin g